MANAJEMEN PONDOK PESANTREN NURUL AMAL DESA KENTENG KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Abdul Khamid; Linda Istiroh (Institut Agama Islam Negeri Kediri, 2019)
Abstract: This research is an attempt to find out the implementation of boarding school management in Nurul Amal Islamic boarding school. The question to be answered through this research is how is the implementation of management management at the Islamic Boarding School in Nurul Amal. supporting factors and inhibiting factors in implementing boarding school management. The research method is a descriptive method with a qualitative approach. Data collection techniques are: observation, interviews, and documentation studies. The subjects of the study were the chairman of the foundation, the boarding school headman, the treasurer, and the clerics who were also administrators in the Nurul Amal boarding school. The research findings show that the management of the Nurul Amal boarding school has been carried out well, in accordance with planning (planning), organizing (organizing), driving (actualling) and supervision (controlling). The reality is that the learning program is carried out, initial planning is carried out with clear vision and mission, organizing with the existence of cadres to build a generation of good-hearted people, and responsibilities carried out by every administrator or cleric, a driver in the management of the Nurul Amal Islamic Boarding School and all employment aspects are institutionalized by the education of the Nurul Amal Islamic boarding school, and supervision of the one-roof Islamic boarding school program by conducting evaluations at the end of each month, as well as the implementation of the learning process in accordance with the assignment assigned to the Ustadz from the chairman of the foundation. The inhibiting factor in the management of the Nurul Amal boarding school is the lack of adequate facilities and infrastructure, especially dormitories and classrooms, causing overload or excess of santri during the new school year as well as supporting factors in Nurul Amal Islamic boarding school,which is strategically located foundation, and community. Abstrak: Penelitian ini merupakan upaya untuk mengetahui pelaksanaan manajemen pesantren di pondok pesantren Nurul Amal. Pertanyaan yang ingin dijawab melalui penelitian ini adalah bagaimanakah pelaksanaan manajemen Pesanren di Pondok Pesantren Nurul Amal. faktor pendukung dan faktor penghambat dalam melaksanakan manajemen pesantren. Metode penelitian adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data adalah: observasi, wawancara, dan studi dokumentasi. Subyek penelitian adalah ketua yayasan, lurah Pesantren, bagian bendahara, serta para ustadz yang juga merupakan pengurus di pondok pesantren Nurul Amal. Temuan penelitian menunjukkan bahwa manajemen pesantren Nurul Amal telah dilaksanakan dengan baik, sesuai dengan perencanaan (planning), pengorganisasian (organizing), penggerak (actualling) dan pengawasan (controlling). Realitasnya terlaksana program pembelajaran, dilakukan perencanaan awal dengan adanya visi-misi dan tujuan yang jelas, pengorganisasian dengan adanya pengkaderan untuk membangun generasi yang berahlaqul karimah, dan tanggung jawab yang diemban dari setiap pengurus atau ustadz, penggerak dalam manajemen pesantren Nurul Amal terkait SDM dan segala aspek ketenaga kerjaan dilembaga pendidikan pondok pesantren Nurul Amal, dan pengawasan program pesantren satu atap dengan mengadakan evaluasi pada setiap akhir bulan, serta terlaksananya proses pembelajaran sesuai dengan pembagian tugas yang telah ditetapkan kepada Ustadz dari ketua yayasan. Faktor penghambat dalam manajemen pesantren Nurul Amal yaitu belum terpenuhinya sarana dan prasarana yang memadai terutama asrama dan ruang kelas sehingga menyebabkan overload atau kelebihan santri pada saat tahun ajaran baru adapun faktor pendukung di pondok pesantren Nurul Amal yaitu lokasi yang strategis serta terjalinnya hubunngan kerjasama yang baik antara yayasan, dan masyarakat.